Somatotroph Adenoma with Dual Transcription Factor Expression. (July 2021) - Pejhan, Shervin; VanUum, Stan; Duggal, Neil; Rotenberg, Brian; Mayich, Michael; Hammond, Robert; Zhang, Qi
Abstract : A 20-year-old male presented with evidence of gigantism/acromegaly. Endocrinological investigations identified elevated growth hormone levels and a failed glucose tolerance test. Imaging revealed a macroadenoma expanding the sella with encroachment on the optic chiasm and cavernous sinuses. Trans-sphenoidal resection was undertaken and a gross total removal was achieved. Histopathological features were typical of a densely granulated somatotroph adenoma with abundant growth hormone expression, scattered prolactin expression and sparse examples of fibrous bodies. Unexpectedly, the adenoma not only expressed PIT-1 but also SF-1 transcription factors. This finding suggests that the adenoma may have been pluripotent. The prognostic significance of this finding is uncertain although the patient is stable from an endocrinological and imaging perspective approximately one-year post-op. A pituitary adenoma of this nature has not been previously reported. The recent literature on atypical transcription factor expression patterns and revisions to the classification of pituitary adenomas will be reviewed. Learning Objectives: Appreciate the rarity of dual transcription factor expression in pituitary adenomas Rationalize the use of transcription factor characterization in the revised WHO classification of pituitary adenomas